ASSESSING THE SAFETY AND EFFICACY OF DIETARY SUPPLEMENTS IN MANAGING DIABETES (The Research of Medical Science Review, 2024)
Diabetes mellitus, a chronic condition characterized by high blood glucose levels, necessitates effective management strategies to prevent complications. Dietary supplements have emerged as a popular adjunctive therapy, but their safety and efficacy in managing diabetes remain subjects of debate. This quantitative study aims to assess the safety and efficacy of various dietary supplements in managing diabetes through structured data collection and statistical analysis. A cross-sectional study was conducted with a sample of 200 diabetic patients, including those with type 1 and type 2 diabetes, who had been using dietary supplements for at least six months. Data were collected through patient medical records and surveys, focusing on blood glucose levels (fasting blood glucose and HbA1c), reported side effects, and interactions with conventional diabetes medications. Statistical analysis included descriptive statistics, paired t-tests, ANOVA, and regression analysis. Key findings indicate that certain dietary supplements, such as chromium, magnesium, and omega-3 fatty acids, significantly improved blood glucose levels. However, the efficacy varied among individuals, and some supplements were associated with mild side effects, such as gastrointestinal discomfort. No significant adverse interactions between dietary supplements and conventional medications were observed. In conclusion, while dietary supplements can be effective in managing diabetes, their benefits are not uniform across all patients. Healthcare providers should consider individual patient profiles when recommending these supplements. Further large-scale studies are recommended to validate these findings and explore the long-term impacts of dietary supplement use in diabetic management.